2015
DOI: 10.1371/journal.pone.0116408
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Leishmania donovani Parasites Complicates Diagnosis of Visceral Leishmaniasis: Comparison of Different Serological Tests in Three Endemic Regions

Abstract: Diagnostic tests for visceral leishmaniasis that are based on antigens of a single Leishmania strain can have low diagnostic performance in regions where heterologous parasites predominate. The aim of this study was to investigate and compare the performance of five serological tests, based on different Leishmania antigens, in three endemic countries for visceral leishmaniasis. A total number of 231 sera of symptomatic and asymptomatic cases and controls from three endemic regions of visceral leishmaniasis in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 35 publications
3
55
2
Order By: Relevance
“…Still, regional differences in antigen performance have been already reported, the performance of rK39 (for the human visceral leishmaniasis) is known to be diminished in subSaharan Africa (Pattabhi et al 2010;Bezuneh et al 2014;Mukhtar et al 2015). Subtle genetic differences in Leishmania strains are sufficient to influence the performance of the recombinant antigens (Abass et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Still, regional differences in antigen performance have been already reported, the performance of rK39 (for the human visceral leishmaniasis) is known to be diminished in subSaharan Africa (Pattabhi et al 2010;Bezuneh et al 2014;Mukhtar et al 2015). Subtle genetic differences in Leishmania strains are sufficient to influence the performance of the recombinant antigens (Abass et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that serological tests based on antigens of a single Leishmania sp. exhibited low diagnostic performance in regions with circulating heterologous parasites [5, 6]. The serological tests, with the exception of the Direct Agglutination Tests (DAT) and Western blotting, exhibit low sensitivity in VL patients coinfected with HIV [79] because of their insufficient immune humoral response.…”
Section: Introductionmentioning
confidence: 99%
“…Additional challenges in diagnostic microbiology include heterogeneity in laboratory methodology, lack of universal standardization or harmonization, and microbial heterogeneity. 16,17 …”
Section: Discussionmentioning
confidence: 99%